Kedudukan Talak di Pengadilan Perspektif Siyasah Syariyah - Miti Yarmunida; Busra Febriyarni (AL-ISTINBATH : Jurnal Hukum Islam, 2019)
The purpose of this discussion is to describe the analysis of siyasah shariah for divorce in court. The understanding is still developing in Indonesian religious and Muslim community figures that divorce is not mandatory in court, divorce in court is only for administrative needs. This research is explanatory research, the source of the data used is library data, data processing by editing, coding, reconstructing and systematizing and analysis using deductive logic. The result of this discussion is that the state has the authority to set regulations that can bring benefit to its people even though explicit divorce in court is not found in Islamic legal norms. But every regulation that is believed to be able to uphold the benefit and reject the interpretation is the implementation of the values of Islamic teachings. The state makes legal rules in marital affairs is to realize justice, certainty and legal benefits for the benefit of society in the field of marriage and in accordance with sharia maqashid.